Penentuan Rute Dan Jadwal Pengiriman Galon Air Minum Dalam Kemasan (AMDK) Dengan Menggunakan Metode Clark And Wright Saving Heuristic - Wahyudi Sutopo; Yuniaristanto -; Srihono - (Performa: Media Ilmiah Teknik Industri, 2007)
PT. Tirta Alam Tunggon is a company that implement direct shipping system for delivering their products to customers. The company delivers their product to customers in seven area. There are Sragen, Karanganyar, Surakarta, Sukoharjo, Klaten and Yogyakarta. The problem solving divided into some steps. The first step is identifying time matrix and saving matrix from each pair of customer. The second step is arranging routes with Clark and Wright Saving Heuristic. Sweep and 2-OPT, 3-OPT methods are use to sequence vehicles trip within route. The third step is to calculate the delivery cost. The delivery cost of the two suggested routes being compared. Suggested route with lower delivery cost is analyze further and use to arrange delivery schedule. The last step is analyzing the suggested route and delivery schedule. Suggested route with 2-OPT, 3-OPT method results lower delivery cost than suggested route with sweep method. Beside that, the arrangement of this suggested route already considers vehicles capacity and work time in the factory.